2021
DOI: 10.5217/ir.2020.00047
|View full text |Cite
|
Sign up to set email alerts
|

Pouchitis in inflammatory bowel disease: a review of diagnosis, prognosis, and treatment

Abstract: patients can be diagnosed with Crohn' s disease (CD) of the pouch. 6 In this review, we discuss the diagnosis and prognosis of pouchitis, risk factors for pouchitis development, and treatment options for pouchitis, including the newer biological agents. CLINICAL COURSE AND DIAGNOSIS OF POUCHITIS Pouchitis is classified as acute or chronic pouchitis. 7 Acute pouchitis is defined as symptoms lasting less than 4 weeks and responding to 2-week courses of antibiotics. Chronic pouchitis is defined as having symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 92 publications
0
29
0
Order By: Relevance
“…Eleven studies employed NLR as a potential tool to predict post-surgical hospital stay or development of various complications in CD [ 84 , 98 , 99 , 100 , 101 ], UC [ 93 , 102 , 103 , 104 , 105 ], or IBD [ 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies employed NLR as a potential tool to predict post-surgical hospital stay or development of various complications in CD [ 84 , 98 , 99 , 100 , 101 ], UC [ 93 , 102 , 103 , 104 , 105 ], or IBD [ 106 , 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a subset of patients with UC who underwent IPAA, Fleshner et al [ 105 ] determined that higher NLR was associated with increased rates of de novo CD as a defined post-surgical complication ( p = 0.03). In patients treated with IFX salvage for steroid-refractory acute severe UC, Con et al [ 103 ] reported a weak but significant correlation between day 3 NLR and colectomy within twelve months ( p = 0.020); NLR value upon admission and on day 1 were not associated with subsequent colectomy ( p = 0.340 and 0.792, respectively). Similarly, Andrew et al [ 93 ] did not find a correlation between NLR and colectomy after hospital admission prior to or one day following IFX salvage therapy (r = −0.01 and −0.01, respectively; correlation method not specified).…”
Section: Resultsmentioning
confidence: 99%
“…In a meta-analysis, the positive predictive value of LGD for concurrent CRC at colectomy was 25.5% and this supported proctocolectomy as a standard treatment of dysplasia in UC [19]. However, proctocolectomy carries high risk of post-operative complications [20]. Ileal pouch anal anastomosis (IPAA) provides chance to save the anus of the patients who underwent proctocolectomy [21,22], and IPAA was possible 89% of UC patients in a Korean multicenter retrospective analysis [23].…”
Section: Surgical Treatment Of Dysplasia In Ucmentioning
confidence: 90%
“…In UC, the approach often involves a restorative proctocolectomy with IPAA due to medically refractory conditions or development of neoplasia. 2 The IPAA is created to avoid a permanent ostomy and to provide patients with an improved quality of life, but it has a well-described risk of acute and chronic complications.…”
Section: S78mentioning
confidence: 99%